A Conceptual Review of Assessing Problem-Solving Skills through Computational Thinking - Boonmee, Thipaphan; Topithak, Krittayakarn (วารสารพุทธจิตวิทยา, 2025)
This article presents concepts, methods, and future directions for assessing problem-solving skills through computational thinking, a crucial 2st century skill. The content covers the theoretical foundations of computational thinking, assessment frameworks, evaluation methods and tools, data analysis and interpretation, challenges and limitations, practical applications of assessment results, and future trends and innovations. The article emphasizes the importance of developing effective assessment tools to support learners in the digital age and provides recommendations for educational institutions to integrate computational thinking into curricula. Furthermore, it analyzes current practices and emerging innovations, making a significant contribution to advancing assessment approaches for problem-solving skills through computational thinking, with particular emphasis on the Thai educational context.